2014
DOI: 10.1097/mrr.0000000000000059
|View full text |Cite
|
Sign up to set email alerts
|

Recovery of hand function with robot-assisted therapy in acute stroke patients

Abstract: In the last few years, not many studies on the use of robot-assisted therapy to recover hand function in acute stroke patients have been carried out. This randomized-controlled observer trial is aimed at evaluating the effects of intensive robot-assisted hand therapy compared with intensive occupational therapy in the early recovery phases after stroke with a 3-month follow-up. Twenty acute stroke patients at their first-ever stroke were enrolled and randomized into two groups. The experimental treatment was p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
72
0
7

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(80 citation statements)
references
References 18 publications
1
72
0
7
Order By: Relevance
“…Sale et al [38] and Hesse et al [39] reported decreases in spasticity and improvements in motor ability; whereas, Masiero et al [10], Chang et al [14], and Fasoli et al [11] reported that spasticity did not significantly decrease despite improvement in upper extremity function and muscle strength.…”
Section: Discussionmentioning
confidence: 99%
“…Sale et al [38] and Hesse et al [39] reported decreases in spasticity and improvements in motor ability; whereas, Masiero et al [10], Chang et al [14], and Fasoli et al [11] reported that spasticity did not significantly decrease despite improvement in upper extremity function and muscle strength.…”
Section: Discussionmentioning
confidence: 99%
“…According to the study reported by Duncan et al21 ) because the recovery of motor function in stroke patients occurs rapidly within the first few weeks of onset, stroke rehabilitation in the early stage has an important role in recovery of motor function. The application of robotics to upper extremity rehabilitation in stroke rehabilitation is increasing, and a variety of associated studies is being carried out17, 18 ) . According to the previous study22 ) , upper extremity robot-assisted therapy improves not only upper extremity function, but also activities of daily living in stroke.…”
Section: Discussionmentioning
confidence: 99%
“…Robot applied in the distal part of upper extremity was effectiveness in reducing spasticity17 ) . Robot applied in the proximal part robot of upper extremity was effectiveness in improvement of motor function and increase in range of motion15,16,17,18, 24 ) . Moreover, whole upper extremity robots showed improved motor function of the proximal upper extremity and activities of daily living and recovery of upper extremity function19 ) .…”
Section: Discussionmentioning
confidence: 99%
“…Task difficulty level, the joints involved and the number of repetitions are adjustable. This kind of robot-assisted therapy proved to be effective in acute5 ) , subacute6 ) , and chronic7 ) state post-stroke according to several clinical trials8 ) .…”
Section: Introductionmentioning
confidence: 98%